ҚАЗАҚ ЖӘНЕ ЖАПОН ТІЛДЕРІНДЕГІ ЕЛІКТЕУІШ СӨЗДЕР - Нурелова, А. М.; Рустемова, А. М. (Journal of Oriental Studies, 2016)
В статье рассматривается особенности звукоподра- жательных слов казахском и японском языках. А также степень изученности, как часть речи, морфологическая структура, виды ономатопе. This article examined the similarities and differences mimetic words in Japanese and Kazakh languages. It also covers issues of research mimetic words in two languages, as part of speech, morphological